A pilot study on the prevalence of peg-shaped permanent maxillary lateral incisors among students of F.G. Calderon Integrated School whose ages range from 7 to 17 years old - Lim, Arleen T.
A peg-shaped lateral (PSL) is a common occurence and is an anomaly. It is described a decrease in the mesiodistal crown diameter towards the incisal edge of permanent maxillary lateral incisor. This paper is a study on the prevalence of the permanent maxillary lateral incisor in F.G. Calderon Integrated School whose total population is five thousand one hundred and ninety-one (5,191). Students whose ages range from 7-17 years old were subjected to ocular inspection. Of these subjects, 112 children were found out to exhibit such anomaly; 53 of which are males and 59, females. The occurrence of bilateral PSL were noted to be higher than either right or left unilateral PSL. Between the occurrence of either right of left unilateral PSL, no significant difference was found. Although the cause of the presence of diastestema, supernumerary teeth, partial anodontia, mesiodens and enamel hypoplasia were not assessed, it was noted that diastema occurred with PSL more often than any other associated condition.